Está en la página 1de 1

P(A')=1-P(A)

1.A&A'-m.e.
2.P(AuA')=P(A)+P(A')x3
3.P(S)=P(A)+P(A') sub.
4.1=P(A)+P(A')
X2
5.4=>-||P(A-B)=P(A)-p(AnB)
1.D: P(A-B)=P(AnB')
AnB & AnB' - m.e.
(AnB)u(AnB1)=1
2.P(AnB)U(AnB')=P(AnB)+p(AnB') sub.
3.P(A)=P(AnB)+P(AnB') sub.
4.P(A)=P(AnB)+P(A-B) sub.
5. 4=>-||P(AuB)=P(A)+P(B)-P(AnB)
D: A&B - m.e.
(A-B)uB = AuB
1. prf 2 =>-||P(AuBuC)=P(A)+..-P(AnB)-..
+P(AnBnC)
1. Rep.B by BuC in prf3
P(AuBuC)=P(A)+P(BuC)-P(An(BuC))
Rep.(An(BuC))=(AnB)u(AnC) => 4
C c D => P(C)<=P(D)
App. prf 2 =>
P(D-C)=P(D)-P(DnC) = P(D)-P(C)